2016
DOI: 10.1108/bij-03-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking presidents’ compensations in institutions of higher education relative to sustainability and other institutional practices

Abstract: Purpose – The purpose of this paper is to investigate the strategic effects of academic institutional factors including environmental, social, and economic sustainability indices on the compensation of the president of an institution of higher education (IHE). The objective is to build relationships among variables to benchmark compensation measures for IHE presidents across US universities to proliferate sustainability initiatives. Some of the variables of the study were environmental sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Pati and Lee [100] analyzed the presidents' compensation in US higher education institutions to benchmark it so that it produces sustainability initiatives. The authors found a significant and positive relationship between the compensation and independent variables, such as environmental sustainability, but the proliferation of sustainability is not among the key criteria for salary.…”
Section: Sustainability Benchmarking In Higher Educationmentioning
confidence: 99%
“…Pati and Lee [100] analyzed the presidents' compensation in US higher education institutions to benchmark it so that it produces sustainability initiatives. The authors found a significant and positive relationship between the compensation and independent variables, such as environmental sustainability, but the proliferation of sustainability is not among the key criteria for salary.…”
Section: Sustainability Benchmarking In Higher Educationmentioning
confidence: 99%
“…Pati and Lee [97] analysed the presidents' compensation in US higher education institutions in order to benchmark it so that it produces sustainability initiatives. The authors found a significant and positive relationship between the compensation and independent variables such as environmental sustainability, but the proliferation of sustainability is not among the key criteria for the salary.…”
Section: Sustainability Benchmarking In Higher Educationmentioning
confidence: 99%
“…Sustainable approaches addressing social, environmental, and financial sustainability are commonly referred to as the "the three pillars" of sustainability (Pati & Lee, 2016). A dozen or more international and national declarations, charters, and initiatives have been written over the past 30 years encouraging HEIs to actively participate in implementing sustainable measures in their institutions, with over 1,000 institutions having signed one or more of the declarations (Lozano et al, 2014).…”
Section: Sustainability In Higher Education Institutions (Heis)mentioning
confidence: 99%